Evaluation of the Sequelae of Untreated Dental Caries Using PUFA Index - Karam H Jazrawi (University of Mosul, College of Dentistry, 2014)
To evaluate (PUFA/pufa) index in assessing the prevalence and severity of oral conditions relat-ed to untreated caries in a group of primary school pupils in Mosul City. Materials and Methods: Dental examination was conducted on 756 school pupils aged 7-12 years old, divided into 3 groups according to age; 7-8, 9-10, and 11-12 years old. Caries was recorded in terms of decayed, missing and filled teeth for both primary teeth (dmft) and permanent teeth (DMFT). The PUFA/pufa index was also recorded for both dentitions regarding the presence of severely decayed teeth with visible pulpal involvement (P/p), ulceration caused by dislocated tooth fragments (U/u), fistula (F/f) and abscess (A/a). Results: Caries experience in the primary dentition was found to be 6.33, 4.75, 1.00, and 4.43 for the three age groups as well as the total sample, respectively. While for the permanent dentition, it was 0.59, 1.18, 3.67, and 1.58, respectively. The PUFA/pufa index recorded the following values for each age group as well as the total sample for permanent and primary teeth respectively; 0.03/2.35, 0/1.66, 0.42/0.58, and 0.12/1.66. The main component in this index for all age groups, and both denti-tions was found to be pulpal involvement. Conclusion: The PUFA index should be seen as a comple-mentary to the current caries assessment index (DMF), with relevant information for epidemiologists and health care planners.